The Effect of Gardening Activities on Cooperation Skills and Skills to Recognize Size Concepts in Children Aged 5-6 Years - Novanti, Tanaya Susilatama; Fitri, Ruqoyyah; Jannah, Miftakhul (Studies in Philosophy of Science and Education, 2025)
The age of 5-6 years is a critical phase in the cognitive and socio-emotional development of children. This study aims to determine the effect of gardening activities on cooperation skills and skills to recognize size concepts in children aged 5-6 years. This study used a quasi-experiment model with a nonrandomized pretest-posttest control group design. The research subjects were 32 children aged 5-6 years, who were divided into 2 groups, namely 16 control group children, consisting of 11 boys and 5 girls, and 16 experimental group children, consisting of 9 boys and 7 girls. The results showed that in the t-test of cooperation ability, the value of p < 0.001, proving p < 0.05 and showing that there was a difference in gain score between the experimental group and the control group. In the t-test of skills to recognize size concepts shows a value of p < 0.001, proving that p < 0.05 and means there is a difference in gain score between the control group and the experimental group. This means that there is an effect of gardening activities on the ability to cooperate and skills to recognize size concepts in children aged 5-6 years.